MOTIVASI BELAJAR MAHASANTRI MELALUI PENDEKATAN BEHAVIORAL MODEL OPERANT CONDITIONING (Studi Kasus di Institut Dirosat Islamiyah Al-Amien Prenduan) - Irawan Hidayat; Totok Agus Suryanto (Universitas Islam Madura, 2022)
Every individual needs the motivation to fulfill the needs of his life. As a basic need, the high motivation of a person can affect the success or failure of achieving goals in life. Likewise in learning, it is very necessary to have a driving force that boosts one's learning stamina so that it remains stable and continuous. As qualitative research with the type of case study research, the sampling technique used was purposive sampling. The main data source of this research is the students of Institute of Islamic Studies Of Al-Amien Prenduan Intensive Program. Data collection techniques using in-depth interviews, observation, and documentation. The data obtained will be analyzed using Miles and Huberman's theory which consists of data reduction, data presentation, and data verification. This study seeks to examine the motivation to learn on students, through a model of behavioral operant conditioning approach. By using the qualitative descriptive method, the researcher found the results of the study with four stages which became a major theme of student learning motivation at IDIA Prenduan. Among them, students are motivated after receiving appreciation (reinforcement), punishment does not learn motivation students decrease (punishment), they are motivated to learn after watching the winners receive awards from campus (shaping) and the absence of awards does not learn motivation student decrease but remains stable. (extinction). Research motivation to learn students through approach behavioral models operant conditioning indicates that reinforcement and shaping influence the motivation to learn students and where punishment and extinction did not have an impact on motivation to learn students of IDIA Prenduan.